(untitled) (Medical Forum Monthly, 2023)
Objective: To determine the frequency of various patterns of partial edentulism in maxilla and mandible. Study Design: Descriptive cross-sectional study Place and Duration of Study: This study was conducted at the Rehmat Memorial Dental Teaching Hospital, Women Medical and Dental College, Abbottabad from 1st June 2020 to 30th December 2020. Materials and Methods: A total 369 patients with at least loss of one tooth, both genders, age from 15 to 70 years were included. Patients with loss of all teeth, with missing third molar, with physical or mental disability were excluded. Partial edentulism was recorded. It was centered on a visual examination of the chosen subjects according to Kennedy’s Classification System. Data was stratified in SPSS 20.0 by age and gender with respect to patterns and analyzed, chi square test at 5% significant level was used. Results: The mean age of the study was 37.51±11.47 years. The females (n=202, 54.7%) were more than males (n=167, 45.3%). In mandible the most pattern was Kennedy’s class III which was present in 111(53.8%) followed by class I having 43(20.8%) patients, class 2 having 28(13.7%) and class IV having 24(11.7%) participants. In maxilla the most pattern was Kennedy’s class III (n=102, 62.5%) followed by class I having 22(13.4%) patients and class II having 21(12.8%) participants, whereas class IV has 18(11.3%) participants. Age groups has significant association with partial edentulism (P<0.05). Conclusion: The most prevalent type of partial edentulism in both maxillary and mandibular arches is Kennedy's Class III. Gender and Age group have significant relationship with the pattern of partial edentulism.